Forty Sixth Meeting of the National Development Council 18th September, 1993 Summary Record - Planning Commission (Planning Commission, 1993)
Shri Pranab Mukherjee, Deputy Chairman, Planning Commission welcomed the participants and briefly highlighted the agenda for the meeting, namely, the reports of four NDC Committees, on Employment, Population, Literacy and Micro Level Planning and involvement of people at grassroot level; follow-up action on the report of the NDC Committee on Austerity and presentation of the status Report on the progress of the transfer of 113 Centrally Sponsored Schemes (CSS) to the State Governments. He also invited the members of the Council to discuss the paper circulated on "Education for All".
Government of India Planning Commission
Government of India Planning Commission